P67 Patients with end-stage liver disease are physically inactive and unable to sustain moderate intensity physical activity: A prospective home-based case-control UK Study. (20th September 2022) - Williams, Felicity R; Quinlan, Jonathan I; Dhaliwal, Amritpal; Rowlands, Alex; Allen, Sophie L; Breen, Leigh; Greig, Carolyn; Elsharkawy, Ahmed; Lord, Janet M; Armstrong, Matthew J
Abstract : Background: Physical frailty is prevalent in end-stage liver disease (ESLD) and is associated with poor clinical outcomes. Increasing physical activity has been used to combat physical frailty, yet current knowledge of daily physical activity patterns is limited to subjective and/or step count reports, making prescription of targeted exercise programmes challenging. Our prospective observational study aimed to compare remotely-monitored daily physical activity patterns with healthy controls (HC), investigate the impact of symptom burden on physical activity, and evaluate the relationship between physical frailty and disease severity with physical activity. Method: Outpatients with ESLD, recruited from the liver transplant waiting list (Birmingham, UK) and age/sex matched HC were provided with a GENEActiv® wrist worn accelerometer for 2-weeks at home. Accelerometer files were extracted, processed and analysed using R-package, GGIR (Version 2.5–0). United Kingdom model for ESLD (UKELD), liver frailty index (LFI), refractory ascites and hepatic encephalopathy (HE) status were recorded. Total inactivity, moderate intensity physical activity (MIPA), total moderate-vigorous physical activity (TMVPA), and intensity for most active continuous time periods were calculated for each valid day and averaged across all valid days. Results: 43 ESLD participants (65% male, mean age 54, UKELD 52, 51% ArLD) and 17 age/sex matched HC were recruited. Participants with ESLD spent a greater proportion of their 24 hr cycle inactive (56% vs 48%, p=0.005) and significantly less time engaged in MIPA (3% vs 7%, p=<0.0001) than HC. During their most active continuous 1 minute, participants with ESLD moved significantly less intensively (313.4 mg vs 691.9 mg, p=<0.001) than HC and were unable to sustain MIPA (>100 mg (slow walk)) for >1 min ( figure 1 ). Those with refractory ascites participated in significantly less TMVPA (24.9 vs 61.0 min/day, p=0.002), whereas there was no difference between those with or without refractory HE (TMVPA 34.4 vs 47.11 min/day, p=0.353). TMVPA was correlated with LFI (r=-0.42, p=0.006), but not UKELD (r=-0.14, p=0.353). Conclusion: Patients with ESLD are significantly less physically active than age/sex matched HC and unable to sustain MIPA. Those with physical frailty and refractory ascites are most severely affected, whereas UKELD is not associated with physical activity levels. These findings can be used to guide much needed exercise interventions in the management of physical frailty in ESLD.